CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

Let f,g:RR be defined, respectively by f(x) = x + 1, g(x) = 2x - 3. Find f + g, f - g and fg.

Open in App
Solution

Here f(x) = x + 1 and g(x) = 2x - 3.

Now (f + g)(x) = f(x) + g(x)

= x + 1 + 2x - 3 = 3x - 2

(f - g)(x) = f(x) - g(x) = x + 1 - (2x - 3)

= x + 1 - 2x + 3 = - x + 4

(f)(g)(x)=f(x)g(x)=x+12x3,x32


flag
Suggest Corrections
thumbs-up
0
Join BYJU'S Learning Program
similar_icon
Related Videos
thumbnail
lock
Introduction to Differentiability
MATHEMATICS
Watch in App
Join BYJU'S Learning Program
CrossIcon